Different Manifestations of Class II Division 2 Incisor Retroclination and their Association with Dental Anomalies. (December 2013) - Pereira, Pedro Mariano; Ferreira, Afonso Pinhão; Tavares, Purificação; Braga, Ana Cristina
Objective: To investigate whether there is an association between dental developmental anomalies (DDAs) and different manifestations of class II division 2 (CII/2) malocclusion incisor retroclination. Design: Retrospective comparative study. Setting: Private orthodontic practice in the regions of Lisbon and Porto, Portugal. Subjects and methods: The sample comprised 115 CII/2 malocclusions distributed into two groups on the basis of incisor retroclination: Group I composed of 48 CII/2 with retroclination exclusively of both maxillary central incisors; Group II composed of 67 CII/2 with retroclination of all four maxillary incisors. Using the initial orthodontic records, it was determined for each patient the presence of the following DDAs: tooth impaction, tooth agenesis, maxillary lateral incisor microdontia, tooth transpositions and supernumerary teeth. Results: Fifty-five per cent of patients were diagnosed with at least one of the DDAs studied. In the total sample the prevalence rates were: 20.0% of palatal maxillary canine impaction, 27.4% of third molar agenesis, and 15.7% of maxillary lateral incisor microdontia. No patient exhibited any transposition or supernumerary teeth. The distribution of the DDAs studied by groups revealed a strong association of palatal canine impaction, tooth agenesis and maxillary lateral incisor microdontia with Group II but not with Group I. Conclusion: The association of DDAs with CII/2 malocclusion is not common to all types of maxillary incisor retroclination, suggesting different etiologic factors among the different manifestations of CII/2 incisor retroclination.